Effect of soil leaching on the toxicity thresholds (ECx) of Zn in soils with different properties - Luyao Qin (Elsevier, 2021)
Currently, the scientific basis for establishing soil environmental criteria is lacking. In order to establish reasonable soil environmental criteria values suitable for soils with different properties, this study selected soils from 16 different sites to determine the toxicity threshold of Zn based on toxicity tests of barley root elongation. In addition, leaching treatments were set up in seven soils with different properties to eliminate the influence of the accompanying anions (Cl-) on the determination of the Zn toxicity threshold. The results indicated that the toxicity thresholds of different soils vary greatly. The EC10 and EC50 ranges of barley root elongation in 16 kinds of non-leached soils were 18.5 mgkg−1 to 1618.7 mgkg−1 and 277.9 mgkg−1 to 3179.8 mgkg−1, respectively. The hormesis effect appeared in the dose response of Zn, and relative barley root elongation reached more than 150%. Leaching significantly reduced the Zn toxicity in acidic soils. The variation ranges of the leaching factor (LF) in the seven soils were LF10 = 1.1–9.3, LF50 = 1.0–3.2. The LF prediction model indicated that pH explained 81.4% of the LF variation (p < 0.01). The soil pH, cation exchange capacity (CEC), and conductivity (EC) explained 97.8% of the EC50 variation in the leached soil (p < 0.01). The results provide reference values for Zn environmental criteria.